1996
DOI: 10.1037/0096-3445.125.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining excellence: Deliberate practice and elite performance in young and older pianists.

Abstract: Two studies investigated the role of deliberate practice in the maintenance of cognitive-motor skills in expert and accomplished amateur pianists. Older expert and amateur pianists showed the normal pattern of large age-related reductions in standard measures of general processing speed. Performance on music-related tasks showed similar age-graded decline for amateur pianists but not for expert pianists, whose average performance level was only slightly below that of young expert pianists. The degree of mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
280
3
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(318 citation statements)
references
References 80 publications
22
280
3
7
Order By: Relevance
“…For instance, Charness's (1981) study of chess players found that high levels of performance could be maintained as performers got older. Other examinations of cognitive-motor experts such as pianists (Krampe & Ericsson, 1996) and typists (Salthouse, 1984) substantiate these findings. These investigations point to the critical role that prolonged involvement (i.e., training) might play in maintaining performance.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…For instance, Charness's (1981) study of chess players found that high levels of performance could be maintained as performers got older. Other examinations of cognitive-motor experts such as pianists (Krampe & Ericsson, 1996) and typists (Salthouse, 1984) substantiate these findings. These investigations point to the critical role that prolonged involvement (i.e., training) might play in maintaining performance.…”
mentioning
confidence: 51%
“…findings suggest that golf might be more closely aligned with cognitive-motor activities such as chess and piano (Charness, 1981;Krampe & Ericsson, 1996) than it is with sports constrained by physiological factors such as aerobic capacity. Sports involving skills that require a finer degree of motor control, necessitating a longer period of acquisition, appear to be more resistant to age-related decline than physiological capacities.…”
mentioning
confidence: 96%
“…Researchers have quantified age-related declines affecting performance with regard to cognitive and physical abilities (Craik & Salthouse, 2000) and have revealed compensatory strategies older adults may use to circumvent typical age-related slowing in specific tasks (Bosman, 1993;Charness, 1981aCharness, , 1981bCharness, , 1981cCharness, Krampe, & Mayr, 1996;Krampe & Ericsson, 1996;Meinz, 2000;Salthouse, 1984). With proper application, this knowledge could inform the design of products, systems, and environments for more effective use by the older population.…”
Section: Knowing the Older Usermentioning
confidence: 99%
“…Salthouse (1984) found such a pattern for expert typists, who were able to compensate for slowed response times by looking farther ahead in the text. And in the musical domain, Krampe and Ericsson (1996) showed that with older pianists deliberate practice serves to 462 …”
mentioning
confidence: 99%